PENYUSUNAN INSTRUMEN TES UNTUK MENGUKUR BAHASA RESEPTIF DAN EKSPRESIF ANAK TUNARUNGU (HEARING IMPAIRMENT) - Dena Tresna Aripiani, - (2020)
A good test measuring tool is one that meets the requirements for the preparation of the test, namely the validity and reliability testing. This study aims to develop a receptive and expressive language instrument for children with hearing impairment. The arrangement of this instrument was adapted from the TOLD-P instrument or a test of language which was modified using Indonesian and made simpler consisting of picture vocabulary, oral vocabulary, and phoneme analysis. The method used in this study used a pre-xxperimental design experimental method with the type of one group posttest. The results of the content validity of this study get a CVR value> 0 that is, 1, while the stability reliability is 0.941 which means it is classified as very high reliability. The test instrument prepared by the researcher has met the good test requirements. Thus the test instrument can be used even for a limited circle. This is because the test instrument is still in the form of an initial draft and has not been tested for a wide range of people, so the instrument is not standardized and needs to be standardized. Keywords:Hearing Impairment, Instrument Arrangement, Test Of Language Development-Primary Third. adanya pengujian validitas dan reliabilitas. Penelitian ini bertujuan untuk menyusun sebuah instrumen bahasa reseptif dan ekspresif bagi anak tunarungu. Penyusunan instrumen ini diadapatasi dari instrumen TOLD-P atau test of language yang dimodifikasi dengan mengggunakan bahasa Indonesia dan dibuat lebih sederhana yang terdiri dari picture vocabulary (kosakata gambar), oral vocabulary (kosakata lisan), dan analysis fonem (analisis fonem). Metode yang digunakan dalam penelitian ini menggunakan metode eksperimen pre-xxperimental design dengan jenis one group postes. Hasil dari validitas isi penelitian ini mendapatkan nilai CVR > 0 yakni,1, sedangkan reliabilitas stabilitas sebesar 0,941 yang artinya tergolong reliabilitas sangat tinggi. Instrumen tes yang disusun peneliti telah memenuhi syarat tes yang baik. Dengan demikian instrumen tes sudah dapat digunakan meskipun untuk kalangan terbatas. Hal ini disebabkan instrument tes masih berupa draf awal belum diujicobakan untuk kalangan yang luas, sehingga instrument belum standard dan perlu distandarisasikan. Kata Kunci : Anak Tunarungu, Penyusunan Instrumen, Test Of Language